Literatur Analisis on the Utilization of PAI Learning Media Applications: A Study of Opportunities and Challenges in Secondary Schools - Velly Sanzi; Muh. Alif Kurniawan (Didaktika: Jurnal Kependidikan, 2025)
The advancement of technology has significantly influenced Islamic Religious Education (PAI) learning. This study aims to analyze the opportunities, challenges, and strategies for utilizing digital learning media applications in secondary schools. Using a literature review approach, this research highlights the potential of learning media to enhance interactivity, participation, and comprehension through engaging and flexible methods. However, challenges such as limited technological infrastructure, low digital literacy among educators and students, and resistance to new teaching methods hinder optimal implementation. Proposed strategies include intensive teacher training, improved infrastructure, relevant content development, and the integration of Islamic values with technology. By addressing these challenges, the use of technology in PAI can foster more effective and innovative learning experiences aligned with the needs of the digital era.